Musical text as ritual object - Schulze, Hendrik (Brepols, 2015)
"Texts often occupy a central role within ritual practices. They serve as prescripts for the organization of the ritual or as an explanation of cosmological backgrounds, as records of ritual performance, or simply as items that are handled and recited during the performance itself. Musical texts may assume some of these roles within certain ceremonial procedures, especially in serving as prescripts for recitation, but also as ritual paraphernalia (for example, where collectors aer concerned). Most importantly, they may serve as records of the performance of those rituals in which music forms a central part, as is the case with opera productions. This volume aims to identify the mechanisms according to which texts, and especially musical texts, may become ritual agents in their own right. It assesses the value of such texts as sources for the reconstruction of rituals, and discusses questions of how ritual aspects of these texts may be represented in modern editions. While the main focus is on music, contributors from a variety of other fields concerned with textual studies (Egyptology, Classical and Modern Indology, Jewish and Islamic Studies) facilitate comparison between different types of texts, emphasizing different approaches to the subject"--Back cover